HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DAN PEMBELAJARAN TIPE TEAMS ASSISTED INDIVIDUALIZATION (TAI) DENGAN PEMANFAATAN LKS DAN ALAT PERAGA PADA MATERI GEOMETRI BANGUN RUANG DI KELAS X SM - Siregar, Ana Febrianti; Jaya, Indra (Universitas Islam Negeri Sumatera Utara Medan, 2016)
This study aims to determine: 1) the results of learning mathematicsusing cooperative learning model type Teams Games Tournament(TGT) with utilization LKS and props, 2) the results of learningmathematics using cooperative learning model Teams AssistedIndividualization (TAI) with utilization LKS and props, 3) comparisonof the results of learning mathematics using cooperative learning modeltype Teams Games Tournament (TGT) and learning types TeamsAssisted Individualization (TAI) with utilization LKS and props. Thepopulation in this study were all students of class X SMA Sinar HusniTerrain academic year of 2015/2016 consisting of three classes. Theresearch sample was determined by random cluster sampling. Thefindings of this study is the use of cooperative learning model typeTeams Games Tournament (TGT) and learning types Teams AssistedIndividualization (TAI) with utilization LKS and props can improvestudent learning outcomes in the geometry of the material geometry inclass X SMA.